Computational study on the antioxidant property of coumarin-fused coumarins. (30th January 2020) - Wang, Guirong; Liu, Yunping; Zhang, Ling; An, Lin; Chen, Ran; Liu, Yin; Luo, Qingquan; Li, Ya; Wang, Han; Xue, Yunsheng
Abstract: Fused coumarins recently attracted strong scientific interest due to their potent pharmacological activities. In this study, density functional theory (DFT) calculations were performed to evaluate the antiradical activities of a series of coumarin-fused coumarins. By calculating the thermodynamic parameters, three primary mechanisms including hydrogen atom transfer (HAT), electron transfer followed by proton transfer (SET-PT) and sequential proton loss electron transfer (SPLET) were examined. It was found that in the gas and benzene phases, the studied compounds prefer to undergo HAT mechanism, while SPLET is more favored in polar media. The results also reveal the possibility of double HAT and double SPLET mechanisms for compound CC-6. Interestingly, a new polycyclic compound was generated by forming a new C5-O5′ bond during the second HAT process at the 5′-OH in CC-6-R6 radical. In addition, the SPLHAT mechanism is proposed as a competitive pathway for radical scavenging by CC-4, CC-5 and CC-6. Highlights: DFT was employed to study the antioxidant activity of coumarin-fused coumarins. The HAT, SET-PT and SPLET mechanisms were investigated. HAT mechanism is dominant in the gas phase. SPLET seems to be more favored in polar media. Double HAT and double SPLET mechanisms as well as SPLHAT are competitive pathways.